Cummins, Inc. : a bump in the road to new emission standards in China (B) - Bagley, Constance E.; Rae, Douglas W.; Rosenthal, Jean W., 1945- (London : Yale School of Management, 2010)
On December 27, 2008, just three days before the date set for implementation of stricter emission standards for diesel engines, China's regulatory agency issued a letter to all diesel manufacturers: Manufacturers could continue to sell engines that met the less stringent NS-II standards until July 1. However, the implementation date had not been moved -- engines manufactured after January 1 had to meet the new NS-III standards. Steve Chapman, Group Vice President -- Emerging Markets and Businesses for Cummins, Inc., knew his company faced a dilemma. Cummins planned to comply with China's new emission standards and was prepared to produce a NS-III engine. It was also ready to manufacture NS-II engines if implementation was postponed. But the Ministry letter made the regulatory situation far from clear.
Originally published in Bagley, C., Rae, D., & Rosenthal, J. (2010). Cummins, Inc.: A bump in the road to new emission standards in China (B). 10-018. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cummins, Inc; Internal combustion engine industry -- Environmental aspects -- China; Air quality -- Standards -- China